Near-Fault Tilted Deformation of Buildings Associated with Coseismic Surface Ruptures in the Shenxigou Section, 2008 Mw 7.9 Wenchuan Earthquake, Eastern Tibet - Hao Xue; Hu Wang; Lin Deng; Kaijin Li; Jinlong Cai (Lithosphere)
The coseismic surface ruptures associated with large earthquakes contribute to severe damage to near-fault buildings through fault deformation. However, previous studies simplified geological conditions and were based mainly on numerical and physical simulations. In other words, the scarcity of large earthquakes, especially for active thrust faults, limits the understanding of the mechanisms of building damage near active faults. Herein, the study selected the 2008 Mw7.9 Wenchuan earthquake as an example. Based on compass measurements, unmanned aerial vehicle data, ground-based lidar mapping, and numerical simulation, the study showed that twelve buildings within the two sides of the fault were damaged by tilted deformation. The study suggests that the closer the buildings are to the fault, the greater the tilted deformation of the buildings. Moreover, the degree of tilted deformation of the buildings on the hanging wall is significantly greater than that on the footwall, indicating an asymmetric characteristic. Furthermore, the azimuth of the tilted deformation of all buildings is consistent toward the northwest and nearly perpendicular to the strike of the coseismic surface rupture, which indicates that the tilted damage to the buildings might be primarily influenced by the thrust deformation. In addition, the simulation results reveal that parameters such as the distance from the fault, angle of the fault, thickness and strength of the sediment can affect the tilted deformation of near-fault buildings. The results enable us to better understand the influence mechanisms of the tilted damage of near-fault buildings and provide a scientific basis for the avoidance of active thrust faults.